C-reactive protein level as a predictor of difficult emergency laparoscopic cholecystectomy. Issue 5 (2nd July 2019) - Ng, H J; Ahmed, Z; Khan, K S; Katbeh, T; Nassar, A H M
Abstract: Background: Studies focused on C-reactive protein (CRP) as a marker of difficult laparoscopic cholecystectomy are limited to small case series. The aim of this study was to evaluate the association between preoperative CRP concentration and difficulty of laparoscopic cholecystectomy in patients admitted with a biliary emergency presentation. Methods: Patients with an emergency admission for biliary disease treated between 2012 and 2017 with a documented preoperative CRP level were analysed. Elective patients and those with other concurrent causes of increased CRP concentration were excluded. The intraoperative difficulty grade was based on the Nassar scale. Statistical analysis was conducted to determine the association of preoperative CRP level with difficulty grading, adjusted for the interval to surgery. Results: A total of 804 emergency patients were included. The mean preoperative peak CRP level was 64·7 mg/l for operative difficulty grade I, 69·6 mg/l for grade II, 98·2 mg/l for grade III, 217·5 mg/l for grade IV and 193·1 mg/l for grade V, indicating a significant association between CRP concentration and Nassar grade ( P < 0·001). Receiver operating characteristic (ROC) curve analysis showed an area under the curve of 0·78 (95 per cent c.i. 0·75 to 0·82), differentiating patients with grade I–III from those with grade IV–V operative difficulty. ROC curve analysis found a cut-off CRP value of 90 mg/l, with 71·5 per cent sensitivity and 70·5 per cent specificity in predicting operative difficulty of grade IV or V. Logistic regression analysis found preoperative peak CRP level to be predictive of Nassar grade I–III versus grade IV–V operative difficulty, also when adjusted for timing of surgery (odds ratio 5·90, 95 per cent c.i. 2·80 to 12·50). Conclusion: Raised preoperative CRP levels are associated with greater operative difficulty based on Nassar scale grading. Graphical Abstract: The association between preoperative serum C-reactive protein (CRP) concentration and difficulty of laparoscopic cholecystectomy was evaluated using a validated grading system in patients admitted with an emergency biliary presentation. A peak preoperative CRP level of 90 mg/l or more was associated with a higher grade of operative difficulty (grade IV–V). CRP and laparoscopic cholecystectomy